2001
DOI: 10.1016/s0008-6363(00)00282-0
|View full text |Cite
|
Sign up to set email alerts
|

Unorthodox angiogenesis in skeletal muscle

Abstract: Physiological angiogenesis within adult skeletal muscle progresses by mechanisms that do not readily conform to the consensus view of capillary growth, derived mainly from observations made during development, pathological vessel growth, or from in vitro systems. The temporal and spatial pattern of growth is determined by the polarity of the mechanical stimulus, i.e., by intra-luminal (increased shear stress) or abluminal (external stretch) stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
231
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(247 citation statements)
references
References 29 publications
16
231
0
Order By: Relevance
“…It should be noted, however, that a difference between the present model and the above-described rodent model, used to study the role of mechanical stretch in angiogenesis (9), is that the present model is not paralleled by mechanical overload, and therefore the impact of stretch is likely to be smaller.…”
mentioning
confidence: 89%
“…It should be noted, however, that a difference between the present model and the above-described rodent model, used to study the role of mechanical stretch in angiogenesis (9), is that the present model is not paralleled by mechanical overload, and therefore the impact of stretch is likely to be smaller.…”
mentioning
confidence: 89%
“…One mechanism by which MVs evolve into capillaries involves intraluminal bridging, a process that was originally discovered in tumour vessels (Nagy et al, 1995), but which has since been found to occur in the angiogenesis induced by Ad-VEGF-A 164 (Pettersson et al, 2000) and healing wounds (Ren et al, 2002), and after chronic vascular dilatation (Egginton et al, 2001). Endothelial cells extend cytoplasmic processes into and across MV lumens, forming transluminal bridges that divide blood flow into multiple smaller-sized channels.…”
Section: Capillariesmentioning
confidence: 99%
“…It has been reported that during the early stages of neovascularization, leading sprouts consisting of collagen IV basement membrane can be observed before endothelial cell proliferation and migration. [35][36][37] To determine whether these sprouts existed in the omentum, immune aggregates and their associated vasculature were identified as before ( Figure 4A, overlay of immune cells in red, and blood vessels in green) and stained simultaneously with anticollagen IV to highlight sprouts ( Figure 4, B and C). In Figure 4B, collagen is observed sheathing most vessels in the aggregate.…”
Section: The Unique Phenotype Of the Blood Vasculature Of The Omentummentioning
confidence: 99%